Application of Dielectric Properties of Dental Material in Non-Destructive Testing - Papezova, Maria; Faktrova, Dagmar (Manufacturing Technology Journal, 2015)
The structural entirety of any biomaterial has to be tested to inhibit to untimely failure and thus maintaining the reliability of the replacement. The knowledge of dielectric properties (relative permittivity, loss factor) of biomaterial without defects in defined microwave frequency range (8-12 GHz) and subsequently comparing properties in defective material as changes in material and classifying the occurrence of inhomogeneities as on the surface so inside the structure. This article deals with possibility to create dental phantom with the same properties as used in practice and dielectric properties measurement method (Hippel method). We made phantom from poly methyl methacrylate (PMMA). PMMA is very commonly used dental material as crown of human tooth or as the crown for intra-osseous dental implantant.
Keywords: Dental material; Dielectric properties; Non-destructive testing